Cr(i)Cl as well as Cr+ are stabilised between two cyclic alkyl amino carbenes1. Issue 5 (20th May 2015) - Samuel, Prinson P.; Neufeld, Roman; Chandra Mondal, Kartik; Roesky, Herbert W.; Herbst-Irmer, Regine; Stalke, Dietmar; Demeshko, Serhiy; Meyer, Franc; Rojisha, Vallyanga Chalil; De, Susmita; Parameswaran, Pattiyil; Stückl, A. Claudia; et al.
<x xml:space="preserve">Abstract</x> Complexes with two and three coordinate chromium(i).